2006
DOI: 10.2151/jmsj.84.763
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Mesoscale Convective Systems over the East Part of Continental China during the Meiyu from 2001 to 2003

Abstract: Hefei Doppler radar observation data over the downstream region of the Yangtze River during the Meiyu period from 2001 to 2003, were analyzed in order to reveal the predominant structural characteristics of meso-b-scale convective systems (MbCSs) around the Meiyu front. Convective and stratiform portions were separated from MbCSs using the bright-band fraction (BBF) method. The daily and yearly mean vertical profiles of radar reflectivity for the convective portion were calculated.Results showed that the verti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 19 publications
(25 reference statements)
3
27
1
Order By: Relevance
“…Convection dominated by warm rain process was found to exist to south of the front (Maesaka 2001). Such convection, whose reflectivity structure was characterized by low altitude of reflectivity peak and low echo top height (15 dBZ ), corresponds to the CMD introduced by Zhang et al (2006). They analyzed 3 years of radar data over the east part of continental China, and concluded that the CMD predominated to the south of the Meiyu front.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Convection dominated by warm rain process was found to exist to south of the front (Maesaka 2001). Such convection, whose reflectivity structure was characterized by low altitude of reflectivity peak and low echo top height (15 dBZ ), corresponds to the CMD introduced by Zhang et al (2006). They analyzed 3 years of radar data over the east part of continental China, and concluded that the CMD predominated to the south of the Meiyu front.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Both LNB and LCL are low (Fig. 8), which are favorable condition for formation of the CMD south of the front (Zhang et al 2006). In the region between the front and 30 km south of the front, the CMD could form in the place where both LNB and LCL are low.…”
Section: Environment For the Cmd South Of The Meiyu Frontmentioning
confidence: 98%
See 3 more Smart Citations